The relationship of neighborhood climate to perceived social support and mental health in older Hispanic immigrants in Miami, Florida. - Brown, Scott C; Mason, Craig A; Spokane, Arnold R; Cruza-Guet, Maria Cristina; Lopez, Barbara; Szapocznik, José (Journal of aging and health, 2009)
This study examines the relationship of neighborhood climate (i.e., neighborhood social environment) to perceived social support and mental health outcomes in older Hispanic immigrants.
Keywords: Adaptation, Psychological; Aged; Aged, 80 and over; Anxiety; Cognition Disorders; Depression; Emigrants and Immigrants; Female; Florida; Hispanic Americans; Humans; Male; Mental Health; Models, Psychological; Residence Characteristics; Self Concept; Social Environment; Social Support; Stress, Psychological; Urban Population